Pneumocephalus and meningitis as a complication of acute otitis media: case report - Ciorba, A (Pacini Editore SpA, 2007)
Otogenic pneumocephalus is a rare condition. The case is described of pneumocephalus and meningitis secondary to acute otitis media. Although the rate of intracranial complications related to middle ear disease is only 0.5 to 4%, mortality still ranges between 5 and 15%.